give me answer and also verify it.
I will mark it as brainliest.
3x-1÷5-x÷7=3
![3x - 1 \div 5 - x \div 7 = 3 3x - 1 \div 5 - x \div 7 = 3](https://tex.z-dn.net/?f=3x+-+1+%5Cdiv+5+-+x+%5Cdiv+7+%3D+3)
Attachments:
![](https://hi-static.z-dn.net/files/d5a/d345ee3af923ea4ee86fb4582bdae912.jpg)
Answers
Answered by
2
Answer:
See this. I have verified it.
Step-by-step explanation:
Hope this will help you..Please mark this answer as the Brainliest and follow me.
Attachments:
![](https://hi-static.z-dn.net/files/d44/6c34db250b4714d174f869cfa38f43e9.jpg)
Similar questions